YIELD AND YIELD ATTRIBUTES OF WHEAT (TRITICUM AESTIVUM. AESTIVUM. AESTIVUM. L) AS INFLUENCED BY MOISTURE REGIMES, L) AS INFLUENCED BY MOISTURE REGIMES, L) AS INFLUENCED BY MOISTURE REGIMES, NITROGEN LEVELS AND WEED CONTROL MEASURES NITROGEN LEVELS AND WEE - SINGH, LAKHAPATI; JOSHI, TANAY; SINGH, RAJESH; JAT, LOKESH KUMAR (The Bioscan, 2018)
Discriminative and judicious use of agricultural inputs is need of the hour. Effect of different moisture regimes, nitrogen levels and weed control measure on the growth and yield of wheat (Triticum aestivum L.) was evaluated in this study. Maximum yield, grain yields (39.29 qha-1) and straw yield (56.26 qha-1) was recorded under 1.0 IW/ CPE ratio. Highest yield and yield attributed were recorded under 150 kg ha-1 doze of nitrogen and in case of weed control measure Sulfosulfuron @ 33 g ha-1 was found to be most effective in controlling weeds and improving yield. Above combination of moisture regime, nitrogen level and weed control method was found to be most effective in improving yield and yield attributes in Wheat.